2017
DOI: 10.1016/j.molstruc.2017.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dicarbonyl(2,4-pentanedionato)iridium(I) decomposition on iron surface and in gas phase: Complex experimental and theoretical study

Abstract: The mechanism of thermal destruction of Ir(acac)(CO)2 as one of the most important MOCVD precursors for Ir coatings deposition was proposed on the footing of the in situ mass spectrometry analysis and quantum chemical modeling.Calculated structural parameters and vibrational spectra of Ir(acac)(CO)2 molecule were found to be in a fairly good agreement with the experimental data.Ir(acac)(CO)2 was found to unlikely decompose in the gaseous phase while its adsorption onto the iron surface leads to major structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This property together with its highest volatility makes this compound a particularly interesting precursor. More detailed information about the thermal behavior of vapors on a heated surface is provided for two Ir(I) volatile complexes: [Ir(cod)Cp Me ] [62] and [Ir(CO) 2 (acac)] [25,63]. Using in situ mass-spectrometry [Ir(cod)Cp Me ] vapors have been shown to be stable up to 280 • C in the absence of a gas-reagent, but the rate of thermolysis was greatly increased at 500 • C (the intensity of ions corresponding to HCp Me and cod increases sharply) [62].…”
Section: Thermal Properties Of Iridium(i) Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This property together with its highest volatility makes this compound a particularly interesting precursor. More detailed information about the thermal behavior of vapors on a heated surface is provided for two Ir(I) volatile complexes: [Ir(cod)Cp Me ] [62] and [Ir(CO) 2 (acac)] [25,63]. Using in situ mass-spectrometry [Ir(cod)Cp Me ] vapors have been shown to be stable up to 280 • C in the absence of a gas-reagent, but the rate of thermolysis was greatly increased at 500 • C (the intensity of ions corresponding to HCp Me and cod increases sharply) [62].…”
Section: Thermal Properties Of Iridium(i) Precursorsmentioning
confidence: 99%
“…For the [Ir(CO) 2 (acac)] complex, experimental results obtained by in situ mass spectrometry [25] were recently supplemented by quantum chemical modeling, which allowed us to present a more complete picture of the process [63]. Calculations have shown that the decomposition of the molecule in the gas phase begins with the cleavage of one of the Ir-O bonds.…”
Section: Thermal Properties Of Iridium(i) Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of theoretical approaches based on DFT calculations in combination with single-crystal X-ray diffraction (SXRD) and IR and NMR spectroscopies provides additional opportunities for studying the energies of crystal lattices and individual molecules of the complexes [ 25 , 26 ], for estimation of the strength of metal–ligand bonds [ 27 , 28 ] and the distribution of tautomeric forms [ 29 ]. From a practical point of view, spectral methods, together with DFT, are widely used to estimate kinetic parameters and probabilities of the cleavage of bonds in the precursor molecules [ 30 ] and to predict the decomposition pathway of the precursor vapors on various substrates during the MOCVD/ALD process [ 31 ].…”
Section: Introductionmentioning
confidence: 99%